2018
DOI: 10.1111/gwao.12333
|View full text |Cite
|
Sign up to set email alerts
|

The missing and needed male nurse: Discursive hybridization in professional nursing texts

Abstract: The role of men in nursing has been of ongoing interest to gender and work scholars who examine the processes that maintain or challenge occupational gender segregation. Drawing on professional nursing texts, the current study moves beyond individual men to investigate organizational practices within nursing that discursively construct the male nurse. Using the rhetoric of ‘equality’ and ‘diversity’, texts frame men in nursing as a missing and needed antidote to projected worker shortages and a homogenous work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 78 publications
(135 reference statements)
2
51
0
Order By: Relevance
“…According to previous studies [ 66 , 67 , 68 , 69 , 70 , 72 ], this motivation from previous experiences [ 40 ] usually directed people’s career perspectives and motivations due to a sense of belonging and positive experiences from lived stories. The current study, therefore, reflected the findings of previous studies and explored the additional sharing and lived stories from this group of male nursing professionals in the United States [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…According to previous studies [ 66 , 67 , 68 , 69 , 70 , 72 ], this motivation from previous experiences [ 40 ] usually directed people’s career perspectives and motivations due to a sense of belonging and positive experiences from lived stories. The current study, therefore, reflected the findings of previous studies and explored the additional sharing and lived stories from this group of male nursing professionals in the United States [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 78%
“…The current findings indicate that although many faced social stigma and social bias due to their gender roles in the nursing profession [ 6 , 40 ], many overcame the discrimination, social stigma, and social bias due to their strong sense of belonging from their childhood experiences and personal goals. First, many of the participants indicated that their sense of belonging (i.e., being a male nursing professional) was always established and firmed due to their positive early life experiences in their hometown [ 65 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Such gender stereotyping of caring is persistent in nursing and male nurses are perceived to be less caring than female nurses 10,11 . Recently, Cottingham, 12 after a discourse analysis of 130 professional nursing texts about male nurses, reported the following core findings. First, men are missing from the discipline of nursing.…”
Section: Introductionmentioning
confidence: 99%